METODE DAN TEKNOLOGI PELAKSANAAN KONSTRUKSI PELABUHAN JETTY - Yuslan Irianie (Universitas Lambung Mangkurat, 2014)
Port is a transport infrastructure plays a major role in promoting the development of an area, where the construction of the jetty port B4 PT. Indocement Tunggal Tbk in Tarjun Kotabaru South Kalimantan is a special port for loading and unloading facilities cement industry which facilitate material transport services and materials production plant. Pre-cast construction technology is an alternative construction material in port construction in Indonesia, the application of precast concrete technology on the pile structure, beams and slabs are practical for construction of the building above the water.Jetty port facility development project B4 is the development of existing ports on specific ports PT.Indocement units operating in Tarjun Kotabaru. Planned length of 56 meters and a width of 26 meters is equipped with a mooring dolphin on the left and two mooring dolphin on the right side, the planned size of the maximum weight that can anchor ship DWT 10,000 tons. The building dock wharf / quay open construction that partly on land and partly above sea level with a combination of methods and construction technology of pre-cast and cast-in-situ.B4 jetty port implementation method starts from the preparatory work for site clearance and preparation base camp and others - seabed dredging works to create a navigation channel and location of the jetty - the jetty construction work comprises the installation of split stone, tetrapod, seawall to the core layer and strengthening leg continued work dock floor comprising pile foundation, installation of precast concrete, bakesting floor plate, floor plate reinforcement and casting dock floor continued maintenance and demolition bakesting - jobs dock facility comprising fender mounting, bollard, mechanical and electrical. Keywords: jetty, pre-cast and cast insitu